Inkjet printing of polyimide insulators for the 3D printing of dielectric materials for microelectronic applications - Zhang, Fan; Tuck, Christopher; Hague, Richard J.M.; He, Yinfeng; Saleh, Ehab; Li, You; Sturgess, Craig; Wildman, Ricky D. (Wiley, 2016)
In this article, we report the first continuous fabrication of inkjet-printed polyimide films, which were used as insulating layers for the production of capacitors. The polyimide ink was prepared from its precursor poly(amic) acid, and directly printed on to a hot substrate (at around 160 °C) to initialize a rapid thermal imidization. By carefully adjusting the substrate temperature, droplet spacing, droplet velocity, and other printing parameters, polyimide films with good surface morphologies were printed between two conducting layers to fabricate capacitors. In this work, the highest capacitance value, 2.82 ± 0.64 nF, was achieved by capacitors (10 mm × 10 mm) with polyimide insulating layers thinner than 1 μm, suggesting that the polyimide inkjet printing approach is an efficient way for producing dielectric components of microelectronic devices. © 2016 The Authors Journal of Applied Polymer Science Published by Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43361.